Tribal Marketing in Sports - Dionísio, J.; Leal, M.; Vinhas da Silva, Rui (II Congreso Internacional de Actividad Fýsica y Deportes, 2014)
Brands that sponsor sports or sports clubs are not always capable of effectively getting close to the fans, and their hearts and wallets. Fan passion does not necessarily therefore transfer over to the brands that endorse a particular club or indeed a sport. The current research seeks to understand how soccer and surf fans see brand sponsorships and their legitimacy and wider acceptability.